Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Sub Sektor Otomotif Yang Terdaftar Di Bursa Efek Indonesia - Eko Cahyo Mayndarto (Politeknik Ganesha Medan, 2022)
Taxes are a very large source of state revenue which is used to finance government expenditures, such as financing government administration, building infrastructure, providing education and health facilities. Taxes are said to be mandatory because they are already stated in the law and there are even regulations governing taxation. Every taxpayer is required to take part so that the growth and implementation of national development can run well. The type of research used is descriptive quantitative analysis method. This study uses secondary data obtained from the documentation. Quantitative descriptive analysis is done by collecting and classifying according to certain criteria or patterns, the data that has been quantified and the analysis is used to get a systematic picture of the contents of a document. Sources of data used in this study is secondary data sources, namely data obtained from existing documents. So that data in finished form has been collected and then processed by other parties and is usually in the form of publications. The secondary data used is in the form of the annual report of companies listed on the IDX in 2015-2019 related to research variables. The data in this study comes from the Indonesia Stock Exchange website and the company's website. The results of the research and discussion can be concluded. There is a partial negative and significant effect between the profitability variable (ROA) on tax avoidance in manufacturing companies in the automotive sub-sector. There is a positive and partially significant effect between company size variables on tax avoidance in manufacturing companies in the automotive sub-sector. There is a simultaneous significant effect between profitability (ROA) and firm size on tax avoidance in manufacturing companies in the automotive sub-sector.